Future boy : Back to the Future and my journey through the space-time continuum - Fox, Michael J., 1961-; Fortenberry, Nelle (Flatiron Books, 2025)
"A poignant, heartfelt, and funny memoir about how, in 1985, Michael J. Fox brought to life two iconic roles simultaneously--Alex P. Keaton in Family Ties and Marty McFly in Back to the Future."-- Provided by publisher.